Adaptation of the working alliance inventory for the assessment of the therapeutic alliance in genetic counseling. Issue 1 (7th February 2021) - Erby, Lori H.; Wisniewski, Tyler; Lewis, Katie L.; Hernandez, Christian; Biesecker, Leslie G.; Biesecker, Barbara B.
Abstract: The concept of therapeutic alliance is central to genetic counseling as the mechanism through which the outcomes of empowerment and effective coping are likely to be achieved. To date, there have been no published systematic assessments of the therapeutic relationship in genetic counseling. We adapted a previously validated measure of the therapeutic alliance to genetic counseling and assessed its reliability and validity. Participants were enrolled in a clinical genomic study where they were randomized to receive education about carrier results via a Web platform or via a genetic counselor and then further randomized to receive genetic counseling (without additional education) or not. We rated the therapeutic alliance from audio recordings of 120 genetic counseling sessions. We modified the observer version of the Working Alliance Inventory (WAI‐O), initially designed to assess therapeutic relationships in psychotherapy. We examined internal consistency reliability by calculating Cronbach's alpha and inter‐rater reliability through both percent agreement and Gwet's alternative agreement coefficient (AC). Regression analyses were used to evaluate the relationship of WAI‐O scores with session length and with the designation of the session as one in which prior education was delivered by the genetic counselor or not. The adapted scale had high‐reliability characteristics with agreement of 88%‐93%, Gwet's AC of 0.84‐0.90, and Cronbach's alpha of 0.89‐0.93 for the three WAI‐O subscales (bonds, goals, and tasks). Although there was no difference in alliance based on whether prior education was provided by the genetic counselor, the total WAI‐O score significantly increased with increasing session length (beta =0.667, p <.001), providing preliminary evidence of construct validity. The WAI‐O that we have adapted can be used reliably with two independent raters to assess the therapeutic alliance in studies of genetic counseling. The initial evidence for construct validity is promising and should be reassessed in future genetic counseling studies using the WAI‐O.